MOBILE-BASED UNIMAS VEHICLE PENAL TYAPPLICA TION - Siti Rasyidah, Mohd Nasir (Universiti Malaysia Sarawak (UNIMAS), 2015)
Nowadays smart phone is one of the necessity in daily life. Android is a mobile platform operating system that allow user to develop, install and use their own application on top of the android framework. Mobile-based UNIMAS Vehicle Penalty Application is one of innovation using android platform to help security officer in UNIMAS to handle student traffic offences information. Using a manual system that used a lot of paper and complex procedure make student traffic offences penalty management still need to be improve. This report elaborate more in recognition technique called Tesseract Optical Character Recognition that can be integrate to be more meaningful application. The application that focused in this report is to identify vehicle plate number using these recognition technology